HUMAN RESOURCE MANAGEMENT STRATEGY IN FACING DIGITAL TRANSFORMATION IN INDONESIAN EDUCATIONAL AND PROFESSIONAL DEVELOPMENT INSTITUTIONS - Imas Imas; Andi Tarlis; Pangestu Tirto Santoso; Lilis Suharti; Leonita Maharani; Yulina Astuti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze human resource management strategies in facing digital transformation at the Indonesian Institute of Education and Professional Development. Digital transformation presents a challenge for organizations in improving service quality, work effectiveness, and human resource capabilities in adapting to technological developments. Therefore, appropriate human resource management is necessary for organizations to adapt to changes in digital-based work systems. This study used a qualitative research method with a descriptive approach. The results show that human resource management strategies in facing digital transformation are implemented through training and development of employee digital competencies, work mentoring, strengthening leadership, and implementing technology-based work systems. Digital transformation has a positive impact on work effectiveness, accelerating administrative processes, facilitating communication, and improving the quality of organizational services. However, this study also found several obstacles, such as limited digital capabilities of some employees, differences in levels of technological understanding, and resistance to changing work culture from manual to digital systems.